The relationship between health literacy and COVID-19 prevention behaviors among people living with HIV - Iman Navidi; Raheleh Soltani (AIDS Research and Therapy)
Abstract Background Health literacy (HL)has been identified as one of the important determinants of healthy behaviors and the health of individuals and communities. The global attempts to control the HIV disease were emphasized, in the midst the new coronavirus disease (COVID-19) emerged as a pandemic. This study aimed to determine HL level and its relationship with COVID-19-prevention behaviors among people living with HIV(PLWH). Methods This cross-sectional study was conducted on 112 PLWH referred to behavioral disorders consulting center in Arak, Iran from May to December 2022. The data collection tool was a questionnaire including COVID-19 prevention behaviors (5 items) and a health literacy instrument (14 items). The data were analyzed using SPSS software version 18 and for all tests, the significance level of α was considered as 0.05. Results The average (SD)age of the participants was 42.9 (10.6) and the education level of 11.6% of the participants were university. The mean score of HL was 3.5 (0.73) out of 5 and 36.6% of them had higher HL. The mean of behaviors was 17.2 (3.4) out of 25 and 53.6 had higher behaviors. The HL had a significant relationship with behaviors (r = 0.48; p < 0.001). Multiple linear regression indicated that HL had a significant association with age (P = 0.002), education (P = 0.046), and economic status (p < 0.001) and explained 32% of the variance of HL. Conclusion According to the findings, HL affected COVID-19-prevention behaviors. Effective educational interventions intended for PLWH based on health literacy can be useful to this extent.